Local Toponymy in Southern Chlef Province: The Village of El Othmania as a Case Study - chihane, radouane (El Omda in Linguistics and Discourse Analysis, 2023)
In this research paper, we will shed light on the local toponymy in the countryside of Chlef province. The village of Athamniya, located in the southernmost of it, is taken as a case for the study. We will try to collect the names of the places in this village within various toponymic fields, monitoring at the same time the connotations of these names. The conclusion is set to conceptualize the approach followed by the inhabitants of the village to name those places. This, in turn, will hand us over the general approach of the spatial toponymy in the south of Chlef province, putting into consideration that the villages, which form a part of it, are similar in terms of topographical relief, and demographics.